The - Fogg, G.E. (Oxford University Press, 1998)
The book is unusual in that it describes and compares the two polar regions, rather than focusing on one. The author's expertise lies in both the Arctic and Antarctica, and his experience encompasses marine and terrestrial ecology. This is the most authoritative and up-to-date book currently available on polar biology. The text provides an excellent introduction for anyone intending to work in research or management in the polar regions. It is also ideal for students in undergraduate and post-graduate courses in biology, ecology, microbial ecology, geography, and conservation